Sottsass - Thomé, Philippe (London : Phaidon, 2014)
De ultieme biografie van de toonaangevende ontwerper Ettore Sottsass, Design museum Gent beschikt over een grote collectie meubilair, glas, keramiek en andere objecten van Sottsass; het boek is zeer mooi uitgegeven met speciale kaft en reproductie van vele tekeningen in verschillende formaten; citaat website uitgever: Perhaps best known as the founder of the Memphis Group in the 1980s – famous for its colourful and flamboyant furniture, ceramics and lighting pieces – Sottsass started his career working as a design consultant for Olivetti. He traveled extensively, particularly in the United States where he found a lot of inspiration. He is quoted as once having said: "When I was young, all we ever heard about was functionalism, functionalism, functionalism. It’s not enough. Design should also be sensual and exciting." This playfulness certainly comes across in his work.
Packed with beautiful images taken from the Sottsass archives, many of which have never been published before and including drawings and sketches from the designer’s countless sketchbooks, this book looks at his entire career. Text by Philippe Thome – an expert on Sottsass’ work – is ordered chronologically and split into periods, each containing sections on the main disciplines that Sottsass pursued in that period along with biographical material.
For example, the 1945 -1949 chapter opens with a biography section followed by texts on sculpture/painting, architecture, interior/furniture, installations and graphic design. The book also includes five short essays, each written by an expert in their field and exploring Sottsass’ work in the following disciplines, placing it in a wider context: - architecture- graphic design- photography- industrial design- collector’s editions. The book is structured according to the narrative text which takes a chronological route through Sottsass’ career, and is broken down into periods, opening with a biographical section and then exploring the disciplines that were most relevant in that period. The book can either be read cover-to-cover as a narrative history, or by discipline, picking up the relative thread under each period.
Engels
boek
Keywords: Sottsass, Ettore; Post-modernisme; Italië